The Impact of Liberalisation and Globalisation on Income Inequality in Developing and Transitional Economies - Giovanni Andrea Cornia (Center for Economic Studies and ifo Institute (CESifo), 2003)
This paper reviews changes in global, between-country and within-country inequality over 1980-2000 against the background of the shifts that occurred in this area during the globalisation of 1870-1914. The paper finds that recent changes in global and between-country inequality are not marked and depend in part on the conventions adopted for their measurement. In contrast, within-country inequality appears to have risen clearly in two thirds of the 73 countries analyzed mainly because of the policy drive towards domestic deregulation and external liberalisation. The paper concludes by analysing the differences between the inequality changes observed during 1980-2000 and 1870-1914.
Keywords: 330; globalisation; globalization